The balances of education reform in Mexico, new regulations for management and teaching work in basic education - Gutiérrez Lozano, Arturo (Education Policy Analysis Archives, 2020)
The Education Reform of 2013, was a government policy implemented in Mexican basic education with the aim of giving children and young people better prepared teachers, well-built and equipped schools, and more and better opportunities for study. Now at the end of the government that implemented the reform, it is appropriate to examine the balances left by this policy in terms of management and labor development for public education teachers. Policy formulations for innovation and change in education and teacher’s work in Mexico are part of the international logic that has generated a new definition of the relations between schools and society. These policies not only imply the existence of new legal frameworks and guidelines for action, but they also institute a political and ideological program that established a new orientation, new objectives, and new will in society. New regulations on the management and practice of public teaching link politics, culture, economy and the state through guidelines that cover the areas of everyday education. The actions of individuals immersed in management, administrative, academic and content organization tasks reconfigure the meaning of teaching based on rationalist effectiveness and efficiency.